Dynamic Approach to Crab Inventory Management in Juata Sea: Balancing Demand and Operational Risks - Nurul Hidayat; Ranianty Ruru; Nurhasanah Nurhasanah; Gilang Ramadhan (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
Harapan Baru is a crab procurement business that serves as a critical link between fishermen and pond farmers. Crabs, as the primary commodity, are subject to significant price fluctuations and quality variations. This study aims to evaluate the economic viability of Harapan Baru's operations by analyzing costs, revenue, and profitability. Employing a critical incident technique, the research found that the First-In-First-Out (FIFO) inventory management method and Economic Order Quantity (EOQ) model significantly enhance operational efficiency. By ensuring timely inventory turnover and optimizing order quantities, these methods mitigate risks associated with demand variability, climate change, and operational challenges. Moreover, the study underscores the essential role of mangrove ecosystems in sustaining crab populations and the economic benefits derived from this natural resource. The integration of technology and SWOT analysis highlights the potential for Harapan Baru to enhance its competitive advantage and contribute to the long-term sustainability of the fisheries industry.